Spirituality in education : professional accounts of the impact of spirituality on education - Gillespie, Aidan (Emerald Publishing Limited, 2021)
Where spirituality in the UK once existed as a shared experience of mutual religious and cultural norms, it has evolved to one where religion, faith and individualism challenges a 'one-size fits all' experience. Considering the dramatic implications this means for British education, Aidan Gillespie puts forward a new definition of spirituality which is unique to educationalists across all settings. With reference to how teachers themselves define and understand the expression of spirituality through their teaching practice, this book draws on narrative accounts from professionals, of faith and none, to illustrate the contested understanding of spirituality and its interaction with professional values and choices. As the author develops the concept of spirituality from a wholly religious tradition and towards one of a shared spiritual component present in each individual, regardless of faith or belief, he also showcases how this might challenge learning spaces with a distinctive religious character. By investigating where the personal conceptualization of spirituality might directly contest the assumed character of faith education, and place tensions on individual teachers with regards to their professional practice, Gillespie demonstrates the importance of this new understanding of spirituality in a culture which pays homage to a largely secular contemporary Britain. Providing enlightening accounts from professionals with wide-ranging experience, this book is appealing reading for teachers, researchers and students of education in the UK as well as internationally.
Includes index.
Keywords: Teaching -- Religious aspects.; Spirituality.; Education -- Religious aspects.; Education, Philosophy, Theory & Social Aspects.; Philosophy & theory of education.; elektronické knihy; electronic books